Introduction to management - Schermerhorn Jr., John R. (Singapore : John Wiley & Son, Inc., 2011)
Introduction to management is designed for this new world of work. It is crafted to help students not just to explore the essentials of the management discipline, but also to understand their great personal potential and accept their responsibilities for developing useful career skills.
Management -- Environment -- Planning -- Organizing -- Leading -- Controlling
Includes index.
Keywords: MANAGEMENT